Microglia response and function in a chronic model of photoreceptor damage - Raghavan, Deepa; Jeakle, Olivia; Berry, Yasmeen; Victor, Majd; Thummel, Ryan (Frontiers in Cell and Developmental Biology, 2025)
BackgroundRetinal neurodegenerative diseases, including diabetic retinopathy and age-related macular degeneration, are characterized by the slow, chronic degeneration of photoreceptors. We previously used a chronic low light (CLL) exposure to model slow photoreceptor degeneration in adult zebrafish. Here, we investigate transcriptional, morphological, and functional responses of microglia in the CLL model.MethodsMicroglia-specific gene expression analysis was mined from our previously reported 3′ RNA-seq data performed at 8 time points during 28 days of CLL exposure. Morphological changes were performed on retinas collected at various time points using immunohistochemistry. Microglial inhibition was accomplished pharmacologically with dexamethasone and genetically using the irf8−/− mutant fish. Finally, we returned the CLL-treated fish to normal light/dark conditions to test whether photoreceptors could recover in the context of chronic stress.ResultsCLL induced dynamic, time-dependent upregulation of microglia-specific genes consistent with pro-inflammatory and pro-resolving function. Dexamethasone treatment reduced microglial numbers and exacerbated rod and cone outer segment damage, whereas irf8−/− mutants exhibited partial protection against photoreceptor damage. Notably, despite prolonged stress and damage during the CLL exposure, photoreceptor outer segments returned to near-baseline morphology after 28 days of normal light/dark recovery conditions.DiscussionOverall, these findings suggest that microglial function in chronic retinal injury is context-dependent as pharmacological and genetic methods of inhibition produced contrasting outcomes depending upon microglial polarization.